Cutaneous and Systemic Adverse Effect of Topical Corticosteroid Misuse on Iraqi Women - Teeba H. Sagban; Jaccob, Ausama Ayob; Abdulla Ayob Yaqoub; Huda. A. Khadim (Iraqi Journal of Pharmaceutical Sciences, 2024)
Topical corticosteroids (TCS) are the most widely prescribed and abused topical medications worldwide. TCs have melanogenic, anti-pruritic, atrophogenic, immunosuppressive effects on the epidermis and sex-hormone-like, in addition to anti-inflammatory activity. Several of these, if used without judgment, may have serious local and systemic negative repercussions. The current study was designed to evaluate the possible local and systemic effects of topical corticosteroid misuse among women in Basrah City and Amara city, Iraq. Totally 125 participants were categorized into three major groups: control individuals, patients who utilize TCs for 1–3 months, and patients with long-term TC use for more than 3 months. A questionnaire was filled out, and a full skin examination was performed by a special dermatologist. Blood was drawn for hematological, hormonal, and biochemical analysis. TCS abuse was linked to the development of skin conditions with various percentages and frequencies, such as erythema, photosensitivity, dryness, acne, atrophy, infections, pigmentation, hirsutism, and rosacea. TCs also have systemic adverse effects in addition to their cutaneous ones, especially with prolonged use. TCS prolongs bleeding time compared to control group. Long-term TCS suppresses ACTH and decreases cortisol concentrations significantly while having no effect on insulin or testosterone levels. Interestingly, TCS significantly reduced serum vitamin D and serum interleukin 6 compared to the normal control group. TCS misuse is a big disaster in Iraq, associated with huge skin impacts and systemic deterioration, including hormonal and hematological consequences that require medical intervention and educational and legal approaches for successful treatment.